Fibre dimension and chemical constituens of rubber tree (Hevea brasiliensis) RRIM 2000 clone series - A. Saffian, Harmaen; Md Tahir, Paridah; Harun, Jalaluddin; Rani, Md. Ali; Ismail, Ismanizam; Lim, Victor K. Sim (2005)
The new rubber wood (Hevea brasiliensis) RRIM 2000 series is introduced by Lembaga Getah Malaysia (LGM) for the production of both latex and timber. These rubber tree clones have been under researched since 2000 thus, information on its wood characteristics and the potential utilization are questionable. The aim of this study is to analyze the fiber morphology and chemical component of new clone RRIM 2000 series. The trees were obtained from LGM Experimentation Station in Besut, Terengganu. The rubber trees were 4 years old felled from 3 different plots, RRIM2002, RRIM2020 and RRIM2025. A total of 30 trees were felled and PB260 rubberwood clone is used as control. The results show that fiber dimension length 1300 μm of those trees RRIM2002, RRIM2020 and RRIM2025 are quite uniform. However, this is a trend that the PB260 clone has highest fiber dimension. The fiber ranges were 1100 μm – 1400 μm for fiber length, 26.70 μm – 33.50 μm for fiber diameter and cell wall thickness is 5.10 μm – 5.80 μm. The chemical component of wood indicated that the PB260 clone has higher of ethanol-benzene (1:2) soluble extractives and lignin content which the RRIM2025 shown higher percentage of holocellulose, alpha-cellulose and ash.